Results of an investigation of the biochemical markers of bone metabolism in males with rheumatoid arthritis - Marina Vasilyevna Letaeva (Современная ревматология)
The paper presents the results of an investigation of the biochemical markers of bone metabolism in males with rheumatoid arthritis (RA). The higher values of bone formation markers suggest that RA patients have increased bone metabolism rates and high bone mass rates, which determine the development of osteoporosis.